2017
DOI: 10.1097/qai.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between HIV Infection, Antiretroviral Therapy, Inflammatory Markers, and Cerebrovascular Endothelial Function Among Adults in Urban China

Abstract: Background-Cerebrovascular risk is increased in people living with HIV infection compared with age-matched uninfected individuals. Cerebrovascular endothelial dysfunction related to antiretroviral therapy and inflammation may contribute to higher stroke risk in HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is associated with opportunistic pathologies due to low activity of the immune system ( Raso et al, 2007 ). Highly active antiretroviral therapy (HAART) is widely recommended for patients with HIV/AIDS as a way to prevent the onset of these pathologies ( Chow et al, 2017 ; Mendicino et al, 2016 ). However, HAART increases the cardiovascular risk of the patients ( Hsue et al, 2009 ; Lipshultz et al, 2003 ; Zareba et al, 2005 ), especially women ( Muyanja et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is associated with opportunistic pathologies due to low activity of the immune system ( Raso et al, 2007 ). Highly active antiretroviral therapy (HAART) is widely recommended for patients with HIV/AIDS as a way to prevent the onset of these pathologies ( Chow et al, 2017 ; Mendicino et al, 2016 ). However, HAART increases the cardiovascular risk of the patients ( Hsue et al, 2009 ; Lipshultz et al, 2003 ; Zareba et al, 2005 ), especially women ( Muyanja et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…50 However, another study did not find an association between endothelial dysfunction, as shown by lower cerebral vasoreactivity on transcranial ultrasound, and inflammatory markers. 48 Exploratory analysis in the latter study did find an association between higher interleukin 6 and worse cerebral vasoreactivity in HIV-positive women, but not in HIV-infected men. These findings underlie the importance of expanding our cohort studies and evaluating potential underlying mechanisms independently in different populations.…”
Section: Cerebrovascular Diseasementioning
confidence: 69%
“…47 Another recent study in an HIV-positive cohort in China found an association between lopinavir/ritonavir and reduced cerebral vasoreactivity by Doppler, suggesting PI use may negatively impact vascular endothelial function. 48 Therefore, PIs likely should be avoided in patients at high risk for cerebrovascular disease.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Vasculitis secondary to infection tends to have a poor prognosis. The most common manifestation of such vasculitis is ischemic infarct, with intracranial hemorrhage (14). Left-sided IE-related CNS complications can be subclinical, asymptomatic events in up to 60-80% of cases (1).…”
Section: Infectious Vasculitis or Arteritismentioning
confidence: 99%